Old masters under the microscope. Technical and material comparison of a 17th c. mural and panel painting assigned to José de Escovar in Southern Portugal - Gil, Milene (2019)
This paper reports the results of a multi analytical research undertaken on a mural and on a panel painting altarpiece authored by José de Escovar in 1603, one of the most productive and controversial painters working for Évora Archiepiscopate at the end of the 16th century and beginning of the 17th century. The two paintings are among his first documented artworks in the region and the only case where both are still in their original architectural location - the Chapel of the Souls in the main church of Vila Nova da Baronia (30 km away from the city of Évora). José de Escovar is a well-known mural painter but not much is still known about his other skills. To better define his craftsmanship, comparison of technical features and painting materials employed on both supports and paint layers was carried out using a multi-analytical setup for in situ analyses and laboratory characterization. The analytical campaign comprised technical photography (UVF-Vis-IR), portable EDXRF, OM, XRD, SEM/EDS, µ-Raman, µ-FT-IR and py-GC/MS. The results showed that although José de Escovar was considered a minor painter, he was clearly acquainted with both painting techniques and the use of different materials in accordance with the pictorial specifications and traditions at the time in Europe.